Tia's Muesli : small dog in the big dogs' lair - Townsend, Stephanie; Mosala, Thabo ([London] : SAGE, 2016)
In April 2011, Hani Niayesh, owner and managing director of Tia's Muesli, received an unexpected phone call from the Pick n Pay hypermarket. The retailer, which formed part of one of South Africa's biggest supermarket chains, invited Tia's to list with it again. In 2009, Niayesh had obtained a listing at a few Pick n Pay outlets in Johannesburg. 18 months later he delisted, disillusioned by his experience. Despite promises of support from the retailer, Niayesh was undecided whether to venture back into what he recalled to be a minefield. Would it make business sense to list with the retailer again?
Originally Published in: Townsend, S., & Mosala, T. (2013). Tia's Muesli: Small Dog in the Big Dogs' Lair. WBS-2013-20. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Tia's Meusli (Firm); Small business -- Finance -- Case studies; Retail trade -- Case studies; Small business -- Management -- Case studies